OCT for Process Monitoring of Laser Transmission Welding: Inline tracking of weld seams enables monitoring and quality control of polymer welding processes. Issue 5 (14th October 2016) - Schmidt, Robert; Ackermann, Philippe
Abstract: Non‐destructive monitoring of laser transmission welding of polymers is a crucial topic in different production areas. Process parameter deviation may result in product failure. Current monitoring often relies on post process or inline methods which are not able to give a qualitative process feedback. Optical coherence tomography (OCT) enables tomographic measurements of transparent material structures (weld seam and defects; Fig. 1) with a few microns resolution. It provides high accuracy for monitoring and quality assurance of pre, inline and post process situations.